2019
DOI: 10.1126/scisignal.aaw2939
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic phosphorylation by NEK6 and NEK7 reduces the microtubule affinity of EML4 to promote chromosome congression

Abstract: EML4 is a microtubule-associated protein that promotes microtubule stability. We investigated its regulation across the cell cycle and found that EML4 was distributed as punctate foci along the microtubule lattice in interphase but exhibited reduced association with spindle microtubules in mitosis. Microtubule sedimentation and cryo-electron microscopy with 3D reconstruction revealed that the basic N-terminal domain of EML4 mediated its binding to the acidic C-terminal tails of α-and β-tubulin on the microtubu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…S4A-C). Previous large-scale proteomic mapping had identified EML2, EML3 and EML4 as potential binding partners of NEK6 (Ewing et al, 2007), while we have recently found that EML4 can be phosphorylated by NEK6 and NEK7 in mitosis (Adib et al, 2019). Western blotting of immunoprecipitates prepared using antibodies against either NEK9 or EML4 confirmed an interaction between endogenous EML4 and NEK9 in extracts prepared from asynchronous U2OS cells (Fig.…”
Section: Eml4 Interacts With Nek9 and Promotes Cell Migrationsupporting
confidence: 63%
“…S4A-C). Previous large-scale proteomic mapping had identified EML2, EML3 and EML4 as potential binding partners of NEK6 (Ewing et al, 2007), while we have recently found that EML4 can be phosphorylated by NEK6 and NEK7 in mitosis (Adib et al, 2019). Western blotting of immunoprecipitates prepared using antibodies against either NEK9 or EML4 confirmed an interaction between endogenous EML4 and NEK9 in extracts prepared from asynchronous U2OS cells (Fig.…”
Section: Eml4 Interacts With Nek9 and Promotes Cell Migrationsupporting
confidence: 63%
“…In the past ten years many novel structures of MAPs bound to the microtubule lattice have been solved (for example ref. 73,[117][118][119][120][121][122][123][124] ). As these structures reveal the precise interaction sites, i.e.…”
Section: ) Tubulin Isotypes and Mapsmentioning
confidence: 99%
“…NEK7 binds to and phosphorylates RGS2 and leads to the localization of RGS2 to the mitotic spindle, which is required for proper mitotic spindle organization and spindle orientation (de Souza et al, 2015). In addition, NEK6 and NEK7 promote the dissociation of EML4 from microtubules in mitosis by phosphorylating the EML4 N-terminal domain at Ser144 and Ser146, which is required for efficient chromosome congression in interphase (Adib et al, 2019). As a potential function of NEK7 in microtube regulation (Cohen et al, 2013), NEK7 was identified to regulate dendrite growth and branching, as well as spine formation and morphology, in part through phosphorylation of the kinesin Eg5/KIF11 (Freixo et al, 2018).…”
Section: Nek7 In the Regulation Of Mitosismentioning
confidence: 99%